Advances in the evaluation of canine renal disease. (September 2016) - Cianciolo, Rachel; Hokamp, Jessica; Nabity, Mary
Highlights: Urinary biomarker analysis is a non-invasive way to help determine the type and severity of renal injury. Serum biomarkers are used to detect decreased glomerular filtration rate. Comprehensive evaluation of renal tissue definitively diagnoses immune complex mediated glomerular disease. Abstract: Many recent advances in the evaluation of dogs with kidney disease have improved our diagnostic algorithms and have impacted our therapeutic strategies. Non-invasive techniques, such as urinary and serologic biomarker evaluation, can help a clinician diagnose and treat a patient that cannot undergo a renal biopsy for clinical or financial reasons. Some biomarkers might help localize the affected structure (glomerulus vs. tubule) and indicate the type or severity of injury present. Although more research is needed, studies indicate that some biomarkers (e.g. urine protein to creatinine ratio and urinary immunoglobulins) can be useful in predicting adverse outcomes. Importantly, the sensitivity and specificity of biomarkers for renal injury should be established and clinicians need to understand the limitations of these assays. If a renal biopsy is performed, then it should be evaluated by a specialty diagnostic service with expertise in nephropathology. A panel of special stains, immunofluorescence for the detection of immunoglobulins and complement factors, and transmission electron microscopy can be routinely employed in cases of glomerular disease. These advanced diagnostics can be used to detect immune deposits in order to definitively diagnose immune complex mediated glomerular disease. Integrating the results of biomarker assays and comprehensive renal biopsy evaluation, the clinician can make informed therapeutic decisions, such as whether or not to immunosuppress a patient.